2013
DOI: 10.4236/psych.2013.49a2001
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Combined Mental and Physical Training in Learning a Complex Motor Skill in Basketball

Abstract: Previous research in sport psychology and rehabilitation suggests that training with motor imagery (mental practice) is a potentially effective strategy to improve motor performance. The goal of the present study was to investigate the benefits of combining mental and physical training in learning a complex motor skill in basketball (the lay-up shot). To this end, sixty female university students were randomly assigned to either mental practice with physical training, or physical training alone. Motor performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
9
0
3
Order By: Relevance
“…Holmes and Calmels (2008, p.433) presented a concept of imagery adapted from Morris et al (2005): "Imagery in the context of sport, may be considered as the neural generation or regeneration of parts of a brain representation/neural network involving primarily top-down sensorial, perceptual and affective characteristics, that are primarily under the conscious control of the imager and which may occur in the absence of perceptual afference functionally equivalent to the actual sporting experience". According to several studies it was verified benefits of imagery capacity in the performance and learning of athletes (Callow and Roberts, 2010;Doussolin and Rehbein, 2011;Anwar et al, 2011;Gaggioli et al, 2013;. For William et al (2012) determining which modality of imagery (kinesthetic, internal or external visual) is the most appropriate to each subject it is vital, as it leads to best results in the application of the imagery technique.…”
Section: Introductionmentioning
confidence: 99%
“…Holmes and Calmels (2008, p.433) presented a concept of imagery adapted from Morris et al (2005): "Imagery in the context of sport, may be considered as the neural generation or regeneration of parts of a brain representation/neural network involving primarily top-down sensorial, perceptual and affective characteristics, that are primarily under the conscious control of the imager and which may occur in the absence of perceptual afference functionally equivalent to the actual sporting experience". According to several studies it was verified benefits of imagery capacity in the performance and learning of athletes (Callow and Roberts, 2010;Doussolin and Rehbein, 2011;Anwar et al, 2011;Gaggioli et al, 2013;. For William et al (2012) determining which modality of imagery (kinesthetic, internal or external visual) is the most appropriate to each subject it is vital, as it leads to best results in the application of the imagery technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a blend of some elements of motion by involving eye-hand, leg and eye movements or hands, feet and eyes simultaneously for maximum and efficient motion [31]. Coordination indicates the player's ability to correctly move all the body required by the task [32]. Coordinative abilities enable the sportsman to do a group of movements with better quality and effect.…”
Section: There Is An Interaction Between Training Methods (Parts and mentioning
confidence: 99%
“…Results of the study showed that there was a significant difference between pre-test score and post-test scores with respect to observation form for the gross motor skills change (p<0.05). Gaggioli et al (2013) investigated the benefits of combining mental and physical training in learning a complex motor skill in basketball. In their study, sixty female university students were randomly assigned to either mental practice with physical training, or physical training alone.…”
Section: Discussionmentioning
confidence: 99%